Advantages and Challanges of the Independent Curriculum in Enhancing Quality of Indonesian Education - Taufik; Firmansyah (LLDIKTI WILAYAH XIII, 2026)
This study discusses the advantages and challenges of the Independent Curriculum (Kurikulum Merdeka) in improving the quality of education in Indonesia. The Independent Curriculum aims to create a more flexible and student-centered learning system that can develop students’ skills and character. It also encourages teachers to use technology as an effective learning tool in this modern era. However, in its implementation, many teachers still face problems such as lack of training, limited learning facilities, and difficulty adapting to technology-based learning. These challenges are more serious in remote areas where access to educational resources is still limited. Despite these obstacles, the Independent Curriculum offers great benefits, such as making learning more active, creative, and relevant to students’ needs. Therefore, improving teacher competence and providing equal educational facilities are important steps to support the success of this curriculum in preparing young generations for future challenges